2017
DOI: 10.1097/aap.0000000000000538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perineural Dexamethasone on the Duration of Single Injection Saphenous Nerve Block for Analgesia After Major Ankle Surgery

Abstract: Perineural dexamethasone as an adjuvant for the single-injection subsartorial saphenous nerve block can prolong analgesia and reduce opioid-requiring pain after major ankle surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…12,17 The present study is the first to estimate the size of the effect of saphenous nerve block after major ankle surgery.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…12,17 The present study is the first to estimate the size of the effect of saphenous nerve block after major ankle surgery.…”
Section: Discussionmentioning
confidence: 92%
“…Not only does the pain arise immediately after surgery, it also seems to persist for a long time. 12,17 The results from our previous saphenous nerve block study indicate that the saphenous pain persists for longer than the duration of a single-injection with bupivacaine-epinephrine and that prolongation of the block duration with adjuvant perineural dexamethasone can reduce opioid consumption during the first 24 hours. 12 The focus on adequate postoperative pain management is important, and clinical studies have shown that early postoperative pain is a strong risk factor in developing chronic pain after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies but one 31 were conducted in Europe. [26][27][28][29][30]32 Sample size ranged from 30 to 98 participants, most of whom underwent arthrodesis, calcaneal osteotomy or ankle replacement procedures. The average age of participants ranged from 39 to 62 yr old across trials.…”
Section: Include Include Includementioning
confidence: 99%